Triple malignancy (NET, GIST and pheochromocytoma) as a first manifestation of neurofibromatosis type-1 in an adult patient - Karolina Poredska; Lumir Kunovsky; Vladimir Prochazka; Jiri Dolina; Miroslava Chovancova; Jakub Vlazny; Tomas Andrasina; Michal Eid; Petr Jabandziev; Petr Kysela; Zdenek Kala (BMC, 2019)
Abstract Background Neurofibromatosis type-1 (NF1), also called von Recklinghausen disease, is a rare genetic disease which can lead to the development of benign or even malignant tumors. NF1 is mostly diagnosed in children or early adolescents who present with clinical symptoms. A curative therapy is still missing and the management of NF1 is based on careful surveillance. Concerning tumors which affect the gastrointestinal tract in patients with NF1, the most common is a gastrointestinal stromal tumor (GIST). Case presentation We present a case of a 58-year-old adult patient with dyspeptic symptoms who was incidentally diagnosed with triple malignancy (pheochromocytoma, multiple GISTs of small intestine and an ampullary NET) as a first manifestation of NF1. The patient underwent surgical treatment (adrenalectomy and pancreaticoduodenectomy) with no complications and after 2 years remains in oncological remission. Conclusion NF1 is a rare genetic disease which can cause various benign or malignant tumors. The coincidence of GIST and NET is almost pathognomonic for NF1 and should raise a suspicion of this rare disorder in clinical practice.